Study of temporal dissociation and atomic excitation rates in a flowing N2 DC discharge and post-discharge. (1st December 2022) - Levaton, J; Klein, A N; Amorim, J; Severo, J H F
Abstract: In this work, we experimentally and theoretically study mechanisms of molecular dissociation and atomic excitation occurring in a flowing nitrogen DC discharge and its post-discharge. A specific discharge experimental condition for the pink afterglow plasma occurrence in the post-discharge tube is analyzed. We employ optical emission spectroscopy (OES) and Langmuir probes to measure the reduced electric field ( E / N ), electron density ( n e ), gas temperature ( T g ) and N2 (X 1 Σ + g ) vibrational temperature ( T v ) in the positive column. OES was also employed in the post-discharge for measurements of relative densities of N( 4 S) and N( 2 D) atoms in the pink afterglow. Two well-established numerical kinetic models, one for the positive column and another one for the post-discharge, were used to calculate the rates of molecular dissociation and atomic excitation as a function of gas residence time in the positive column and also in the nitrogen post-discharge. We analyzed the role of 13 molecular dissociation mechanisms, and 8 atomic excitation mechanisms in the positive column and pink afterglow. Results demonstrate that the positive column dissociation processes are dominated by the direct electron impact mechanism in the earlier discharge gas residence times and that, for longer times, reactions between electronically excited states and N2 (X 1 Σ + g, v ) vibrational states become the dominant dissociation mechanisms. It is also observed that dissociation processes occurring in the pink afterglow present relevant rates as compared to the same processes occurring in the positive column, demonstrating the high effectiveness of such processes in the post-discharge. The N( 2 D) and N( 2 P) excitation mechanisms are also examined. We observe that molecular dissociation and atomic excitation mechanisms strongly depend on the N2 (X 1 Σ + g ) vibrational distribution function of the discharge and post-discharge.